"Om jag ej får gå med byxsor kan jag inte lefva": Therese Andreas Bruce och kampen för en manlig identitet i 1800-talets Sverige - Littberger Caisou-Rousseau, Inger (Tidskrift för litteraturvetenskap, 2013)
”If I Am Not Allowed to Wear Trousers I Cannot Live”. Therese Andreas Bruce and the Struggle for a Male Identity in Nineteenth-Century Sweden This article is a study of an autobiographical text written by Andreas Bruce (1808–1885) at the end of his life. He was born to an aristocratic family as a girl named Therese. At the age of sixteen, the young woman declared that it was absolutely necessary for her to live her life as a man. A distinguished doctor examined Therese, finding that she was a kind of hermaphrodite, more male than female. This article highlights that the main theme of the autobiography is the necessity for Bruce to prove to himself and other people that, although he is not ”a complete man”, he is capable of managing everything that a man is expected to endure, and to do so with extraordinary courage. In this sense, Bruce exemplifies Bourdieu’s thesis that virility is a highly relational quality constructed before other men and against femininity for fear of the female potential inside man himself. While Bruce is physically weaker than other men, he compensates through mental strength, acting in a consistently courageous manner. This, at least, is the image he wishes to project. The most serious threat to this image was his pregnancy, when he had been living as a man for about thirteen years. Bruce’s predicament was dire, but he was also alive to the possibilities of his unique situation and had the capacity to utilize them. His Christian convictions, which grew stronger towards the end of his life, also played an important role. It is ironic and regrettable that his tombstone was engraved with his female initials, rather than his male initials, in an act that was certainly not in compliance with Bruce’s desires.